A preliminary investigation into the use of an auditory brainstem response (ABR) simulator for training audiology students in waveform analysis - Dzulkarnain, Ahmad Aidil Arafat; Wan Mohd Pandi, Wan Mahirah; Wilson, Wayne.J; Bradley, Andrew P.; Sapian, Faizah (Informa Health Care, 2014)
Objective: To determine if a computer simulation can be used to improve the ability of audiology students to analyse ABR waveforms. Design: A pretest-posttest, quasi-experimental design was used. All participants completed a pretraining examina- tion of their ability to analyse ABR waveforms, eight hours of ABR analysis training over eight weeks using one of three training modes — manual, simulator or combined manual and simulator training, and a posttraining examination of their ability to analyse ABR waveforms. Study sample: Fourteen third-year audiology students (13 female, one male, aged 21 to 22 years) participated in this study. Results: Participants who completed the manual or the combined manual and simulator training achieved significantly higher normalized gain scores on their ABR waveform analysis examinations compared to those who completed the simulator train- ing (p0.05). Conclusions: Our findings suggest that the improvements seen in the ability of these audiology students to analyse ABR waveforms were driven primarily by the manual training. The minimal improvements seen in the students who received the simulator training suggest that face-to-face instruction could be required to enhance the ability of audiology students to analyse ABR waveforms.